2019
DOI: 10.1128/jvi.01709-18
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Differences between Functional Human Immunodeficiency Virus Envelope Glycoprotein Trimers and Stabilized Soluble Trimers

Abstract: Binding to the receptor CD4 triggers entry-related conformational changes in the human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein (Env) trimer, (gp120/gp41)3. Soluble versions of HIV-1 Env trimers (sgp140 SOSIP.664) stabilized by a gp120-gp41 disulfide bond and a change (I559P) in gp41 have been structurally characterized. Here, we use cross-linking/mass spectrometry to evaluate the conformations of functional membrane Env and sgp140 SOSIP.664. Differences were detected in the gp120 trimer ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 106 publications
(210 reference statements)
2
30
0
Order By: Relevance
“…Despite its relatively poor processing, we found that the EnvΔ712 DS mutant could mediate a moderate level of cell-cell fusion in a reducing environment, and this allowed us to investigate the conformation of the functional EnvΔ712 DS glycoprotein. Although these studies were performed with the cytoplasmic tail-deleted EnvΔ712, the ectodomain conformations of the EnvΔ712 and full-length Env from many HIV-1 strains, including HIV-1 JR-FL , are similar (42,101,132). Consistent with this similarity, the unmodified full-length Env and cytoplasmic tail-deleted EnvΔ712 exhibited nearly identical antigenic profiles ( Fig.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Despite its relatively poor processing, we found that the EnvΔ712 DS mutant could mediate a moderate level of cell-cell fusion in a reducing environment, and this allowed us to investigate the conformation of the functional EnvΔ712 DS glycoprotein. Although these studies were performed with the cytoplasmic tail-deleted EnvΔ712, the ectodomain conformations of the EnvΔ712 and full-length Env from many HIV-1 strains, including HIV-1 JR-FL , are similar (42,101,132). Consistent with this similarity, the unmodified full-length Env and cytoplasmic tail-deleted EnvΔ712 exhibited nearly identical antigenic profiles ( Fig.…”
Section: Discussionmentioning
confidence: 75%
“…The cross-links observed in the sgp140 SOSIP.664 glycoprotein were completely compatible with multiple reported sgp140 SOSIP.664 structures (57)(58)(59)(60); thus, the available structural models accurately describe the conformation of sgp140 SOSIP.664 trimers in solution. In contrast, many cross-links observed in the membrane Env trimer could not be explained by the available high-resolution structural models of sgp140 SOSIP.664 trimers (101). Fourth, after comparing the results of double-electron-electron resonance (DEER) spectroscopic analyses of sgp140 SOSIP.664 trimers with the results of smFRET studies of native Env on HIV-1 virions, Stadtmueller et al speculated that existing high-resolution structures of HIV-1 Env trimers may represent state 2 conformations (127).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations